Rancang Bangun Alat Pengupas Kulit Kopi Mentah Dengan Metode Rapid Upper Limb Assesment (RULA) Untuk Mengurangi Keluhan Muskoloskeletal - Ratih Rahmahwati; Yopa Eka Prawatya; Bartolomeus Lumbantoruan (Operations Excellence: Journal of Applied Industrial Engineering, 2021)
The people of West Kalimantan, especially in Punggur, Sungai Kakap, Kuburaya execute the grinding process of coffee beans with two types of processing, namely dry processing and wet processing. In the process of wet processing, there are problems, one of them is when grinding raw coffee process before the drying process. The process of grinding raw coffee is carried out with non-ergonomic equipment that causing the workers to have musculoskeletal disorders complaints, the workers are bending over so that they cannot work for a long time, and low productivity because workers have to separate the beans from the coffee skin which takes a long time. This study aims to analyze the level of musculoskeletal disorder risk experienced by workers when using a raw coffee grinder using the Rapid Upper Limb Assessment (RULA) method. In addition, an anthropometric principle was carried out to determine the size of the tool so it can be used in an ergonomic position and can get a good working posture recommendation when using the machine. Based on RULA analysis using CATIA, show a score of 6 when lifting coffee from the grinder, grinding raw coffee, and taking the coffee grind. The result of RULA indicates that repairs and changes are needed quickly because the work posture produced by the coffee grinder is not ergonomic. Meanwhile, the results of RULA analysis using a coffee grinder after the design showed a score of 3 when lifting coffee from the grinder, a score of 4 when grinding raw coffee, a score of 3 when taking the results of the coffee grind. The score shows that the resulting posture is ergonomic and feasible to apply.